Synergistic effect of p-type and n-type dopants in semiconductors for efficient electrocatalytic water splitting. Issue 46 (15th November 2022) - Kutlusoy, Tugce; Divanis, Spyridon; Pittkowski, Rebecca; Marina, Riccardo; Frandsen, Adrian M.; Minhova-Macounova, Katerina; Nebel, Roman; Zhao, Dongni; Mertens, Stijn F. L.; Hoster, Harry; Krtil, Petr; Rossmeisl, Jan
Abstract : Co-substituting a stable material, e.g. TiO2, with both n- and p-type dopants, allows tuning its reactivity to activate the material for oxygen evolution. This opens up a new design avenue for acid water electrolysis electrocatalysts. Abstract : The main challenge for acidic water electrolysis is the lack of active and stable oxygen evolution catalysts based on abundant materials, which are globally scalable. Iridium oxide is the only material which is active and stable. However, Ir is extremely rare. While both active materials and stable materials exist, those that are active are usually not stable and vice versa . In this work, we present a new design strategy for activating stable materials originally deemed unsuitable due to a semiconducting nature and wide band gap energy. These stable semiconductors cannot change oxidation state under the relevant reaction conditions. Based on DFT calculations, we find that adding an n-type dopant facilitates oxygen binding on semiconductor surfaces. The binding is, however, strong and prevents further binding or desorption of oxygen. By combining both n-type and p-type dopants, the reactivity can be tuned so that oxygen can be adsorbed and desorbed under reaction conditions. The tuning results from the electrostatic interactions between the dopants as well as between the dopants and the binding site. This concept is experimentally verified on TiO2 by co-substituting with different pairs of n- and p-type dopants. Our findings suggest that the co-substitution approach can be used to activate stable materials, with no intrinsic oxygen evolution activity, to design new catalysts for acid water electrolysis.